The cultural practice of immigrant filmmaking : minor immigrant cinemas in Sweden 1950–1990 (2019)
Beginning soon after the birth of the seventh art, a series of acclaimed Swedish directors, actors and cinematographers worked in an arresting and immediately recognizable landscape to create one of the world’s most prominent national cinemas. Its global influence was promoted by the emigration of many illustrious artists to other countries in Europe and to the United States. Before the Second World War, Victor Sjöström’s and Greta Garbo’s work in Hollywood paved the way for the post-war international reputation of Ingmar Bergman, Liv Ullmann, Bibi Andersson and Sven Nykvist in one register and Vilgot Sjöman and Bo Widerberg in another. More recently, the success of Män som hatar kvinnor (The Girl with the Dragon Tattoo) and subsequent adaptations of Stieg Larsson’s ‘Millennium’ series of novels again prove Sweden to be a seminal cinematic wellspring. For several generations of cinephiles across the world, ‘Svensk Filmindustri’ has been one of the best known and best loved logos on the silver screen.